Right to Primary Education and Disadvantaged Children in Urban Slums: Context and Concerns - Dutta, Rajdeep; Dey, Joyashri; Dutta, Subhabrata (Voices of Teachers and Teacher Educators, 2022)
Urban slums are a widespread phenomenon and appear in almost all cities worldwide. Slum dwellers are underprivileged sections of urban society and are deprived of basic livelihood, health, and education. Education is a fundamental human right and a key indicator of a country’s overall development. Societal progress and nations’ socio-economic development depend upon their citizens’ educational status. The Right to Education Act 2009 provides free and compulsory education to all with no discrimination. Children in slums were found to be more silently excluded, regularly irregular, and dropouts in elementary school stages than children in non-slum areas. Mostly, these issues are left unaddressed, but considering the value of education to society, they need to be addressed immediately. Hence, the current study focuses on urban slum children’s rights to education and the challenges they face in their living conditions, homes, and social environments in the context of education. Also, an effort was made to cover the role of the non-formal education centre (under Sarva Shiksha Abhiyan) and intervention in promoting education. Besides, the study underlines the implications for the upcoming research and practice interventions for deprived slum children.